“God Damn This War”: Virginia Woolf's Struggle for Peace between the Wars - Velid BEGANOVIĆ (E-REA)
This paper analyses Virginia Woolf's non-fiction and fiction writings in the years surrounding three wars which had a direct impact on her life: the First World War which shaped her generation and made her question the sanity of the society that went on living as if millions had not perished in vain, the Spanish Civil War to which she lost her nephew Julian Bell and which would become one of the driving forces for her book-length anti-war essay Three Guineas (1938), all the way to the Second World War that would eventually play a significant role in her ending her life. How can an experience (such as war) be communicated to others in writing is a preoccupation throughout, and I trace Woolf’s private and public views as they change over time, comparing them to those of her contemporaries, such as her husband Leonard Woolf, Katherine Mansfield and Stephen Spender, as well as juxtaposing them with Ludwig Wittgenstein’s propositions from the last part of his Tractatus Logico-Philosophicus which arrives at kindred conclusions.